Dynamic tunability enhancement of reflectarray antenna using non-homogeneous dielectric materials - Dahri, Muhammad Hashim (2014)
The conventional antenna systems require the mechanical movement of beam scanning antenna to meet the demands of emerging field of communications. To overcome the flaw of the mechanical movement an electronically tunable reflectarray antenna based on non-homogeneous properties of substrate materials has been introduced. This research study provides a thorough investigation on the tunability performance of reflectarrays designed in X-band frequency range. The objective of this work is to demonstrate the functionality of an active reflectarray antenna with optimized loss performance and enhanced dynamic phase range. Different types of reflectarray resonant elements such as rectangular, dipole and ring are discussed here with different design configurations based on their ability of frequency tunability and dynamic phase range. Commercially available computer models of CST Microwave Studio and Ansoft HFSS have been used to investigate the phase agility characteristics of reflectarray resonant elements printed above various nonhomogeneous materials (0.17≤ ∆ε ≤0.45). The analytical approach has been used to develop equations for progressive phase distribution and frequency tunability of individual reflectarray element which is validated by CST simulations. The results obtained from theoretical investigations have been further validated by experimental implementations. An optimized configuration of non-homogeneous Liquid Crystal (LC) material with 0.5 mm thickness below the resonant element has been designed and tested by waveguide scattering parameter measurements. An external bias voltage of 0V to 20V has been applied across the LC substrate of individual resonant elements in order to obtain the electronic tunability. The three resonant elements namely rectangular, dipole and ring offer a measured dynamic phase range of 95°, 153° and 197° respectively at 10 GHz using the proposed design configuration. Moreover, the ring element attains a 107% higher dynamic tunability with a 56% reduction in the reflective area as compared to rectangular element.